ANALYSIS OF FINANCIAL REPORTS OF PT. BISI INTERNASIONAL TBK IN 2024 - Savina Alhidrah; Yessi Safitri; Dara Aulia; Afdhalul Ramadhan; ichsan (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the financial performance of PT BISI International Tbk for the year 2024 using financial statement analysis. The research focuses on evaluating the company's financial condition through liquidity, solvency, profitability, activity, and market ratios based on audited consolidated financial statements. The method applied is descriptive quantitative analysis by calculating and interpreting relevant financial ratios, including current ratio, quick ratio, debt to asset ratio, debt to equity ratio, gross profit margin, net profit margin, return on assets, return on equity, total asset turnover, inventory turnover, receivable turnover, earnings per share, price earning ratio, dividend per share, and dividend payout ratio. The results indicate that PT BISI International Tbk has a very strong liquidity position and a conservative capital structure with low financial risk. Profitability ratios show the company's ability to generate stable profits, although efficiency in asset utilization and inventory management still requires improvement. From the market perspective, the company demonstrates positive performance as reflected by favorable earnings per share and a balanced dividend policy. Overall, the analysis shows that PT BISI International Tbk is in a healthy and stable financial condition, making it attractive to investors while still providing opportunities for operational efficiency enhancement.